Evaluation of turbidity removal using Moringa oleifera lam. seeds - Bagh, Mohammad Golestan (2010)
Many studies on Moringa oleifera have proven that its seeds are highly effective as a natural coagulant in turbidity removal. This study examined various reviews and evaluations, especially of storage and extraction methods, and of the effects of varying water turbidity levels on the efficiency of Moringa oleifera in turbidity removal. It is worth highlighting that almost all reviewed works investigating the coagulation effects of Moringa oleifera used the jar test as a common, standard laboratory procedure. First, performance and efficiency of various parts of the Moringa oleifera fruits and seeds from different sources on turbidity removal efficiency were investigated. Results showed that Moringa kernels were the only plant part that exhibited coagulation properties. On the other hand, the results also revealed that seeds collected from different sources varied in the efficiency of turbidity removal. Next, different methods of extracting the active ingredient from the seeds under different pretreatments were investigated. Comparison between sodium chloride (NaCl) and distilled water methods of extraction of Moringa oleifera seeds revealed that salt extraction was more efficient, with a dosage 3.5 times lower, than the water extraction in bringing the active coagulant ingredient of Moringa into the aqueous phase. Furthermore, shell-free Moringa oleifera seeds were more effective in turbidity removal than the seeds. When compared with alum, the turbidity removals achieved in coagulation process using Moringa oleifera seeds were almost identical and around 97%. In addition to this, turbidity removal efficiency was investigated for shell-free Moringa oleifera seeds under different storage conditions; i.e., open and closed containers at room temperatures (27 °C), and durations of storage of 0, 2, 4, 6 and 8 weeks from the time the seeds were picked from the trees. The results of this study additionally indicated that varying the storage conditions and periods of the shell-free Moringa oleifera seeds resulted in no significant differences between open and closed-container storage and turbidity removal remained between 97% - 94.2%. Next to this and based on the above-mentioned findings, the effects of different water quality parameters such as pH, bicarbonate-alkalinity, salinity and calcium and magnesium hardness, on turbidity removal were examined. Results showed that within the range of the pH values considered (pH = 5 - 9) the residual turbidity did not change significantly; it demonstrated an insignificant increase with pH from 5.7 NTU to 8.2 NTU. Moreover, the results of this work demonstrated that the different investigated levels of alkalinity, hardness and salinity had no significant effects on turbidity removal. For example, increasing the HCO3- concentration progressively from 25 to 250 mg HCO3-/ L affected a slight increase in turbidity removal from 92.35% to 94.7%. As to calcium hardness, a minute decline in turbidity removal from 95% to 93.8% was observed upon progressive increases of the levels of calcium hardness from 25 to 250 mg Ca2+/L. Increasing the levels of magnesium hardness successively from 25 to 250 mg Mg2+/L too reduced the residual turbidity; however, to an extent somewhat higher (95.3% to 91.2%) than the corresponding decrease obtained with the attendant levels of calcium hardness. Lastly, increasing the concentration of NaCl in the tested water from 25 to 250 mg NaCl/L lead to a mild decline in turbidity removal; 96.7% to 93.8%.The properties of dried stock component and the effect of temperature and storage on dried stock solution on the efficiency of turbidity removal were also investigated. Stock solutions of Moringa oleifera were either freeze-dried or oven-dried at two temperatures, 70ºC and 95ºC. The results obtained indicated that the freeze-dried powder was a more effective coagulant than the heat-dried powder with the 96% turbidity removal. Storage of the powder up to two months confirmed that duration of storage of the powdered freeze-dried stock solution did not significantly affect turbidity and reduced from 96% to 93.8%. In conclusion, the findings of this study agree well with the findings of earlier studies on the potential use of Moringa oleifera as a natural coagulant, particularly as an attractive alternative to chemical and synthetic coagulants. It is a user-friendly and environmentally-friendly coagulant with offering 97% turbidity removal efficiencies.